Effects of different altitudes on the structure and properties of potato starch - Hu, Tingyuan; Yang, Hongkun; Zhang, Kaiqin; Hafsa, Cheema Nazir; Fang, Xiaoting; Ma, Haiyan; Liao, Jiangxiu; Zheng, Shunlin (Frontiers in Plant Science, 2023)
The environment is the key factor affecting the quality of potato starch. To investigate the effects of different altitude cultivation locations on the molecular structure and physicochemical properties of starch, two potato varieties, Jiusen No.1 B1 and Qingshu No.9 B2, were planted in three different altitude zones: A1 at low altitude (Chongzhou 450 m), A2 at middle altitude (Xichang 2800 m), and A3 at high altitude (Litang 3650 m). The results showed that the average volume, number, surface area diameter, average branched polymerization degree, crystallinity, and gelatinization temperature of two potato granules in high altitude areas were significantly lower than those in middle and low altitude areas were, and the gelatinization performance of potato starch was affected according to the correlation of starch structure characteristics. Potato starch with more short-branched chains and less long branched chains resulted in a lower gelatinization temperature in high altitude areas. The results showed that Jiusen No. 1 and Qingshu No. 9 were mainly affected by accumulated radiation and accumulated rainfall in Litang, a high altitude area, and by effective accumulated temperature in Xichang, a middle altitude area. This study quantified the influence of meteorological factors on the main starch quality of potato tubers. The results can be used as a theoretical basis for the scientific planting of high-quality potatoes.